Differentiation between dogs with thrombosis and normal dogs using the overall hemostasis potential assay. Issue 3 (25th January 2016) - Dengate, Anna L.; Morel‐Kopp, Marie‐Christine; Beatty, Julia A.; Barrs, Vanessa; Braddock, Jody A.; Churcher, Richard K.; Wilson, Bethany J.; Ward, Christopher M.
Abstract: Objective: To determine whether the overall hemostasis potential (OHP) and calibrated automated thrombogram (CAT) were significantly different between dogs with thrombosis and normal dogs. Animals: Ten dogs with clinical evidence of thromboembolic disease had both OHP and CAT performed. Forty healthy control dogs had OHP performed, and 23 of these also had CAT performed. Measurements and Main Results: Dogs with thrombosis had significantly higher OHP ( P = 0.003), overall coagulation potential ( P = 0.0001), and maximum optical density (Max OD, P < 0.0001) than normal dogs, and a significantly longer delay in the start of clot formation ( P = 0.01). Max OD was higher than established reference intervals in 80% of the dogs with thrombosis. Using the CAT assay, dogs with thrombosis had a significantly longer lag time than normal dogs ( P < 0.001). Plasma fibrinogen concentration correlated positively with overall coagulation potential, OHP, Max OD, and the slope of the OHP curve ( P < 0.05), and was increased in 90% of dogs with thrombosis. Conclusions: The OHP assay findings were significantly different between normal dogs and those with thrombosis. CAT did not detect any significant differences between these populations of dogs, other than the lag time of the assay.